Vibration in continuous media - Guyader, Jean-Louis. ([S.l.] : Wiley-ISTE, 2006)
Three aspects are developed in this book: modeling, a description of the phenomena and computation methods. A particular effort has been made to provide a clear understanding of the limits associated with each modeling approach. Examples of applications are used throughout the book to provide a better understanding of the material presented.